Status of cassava begomoviruses and their new natural hosts in Nigeria - Ogbe, F.; Dixon, Alfred G.O.; Hughes, J.D.; Alabi, O.J.; Okechukwu, R.U. (Scientific Societies, 2006)
A diagnostic survey was conducted in 2002-03 to determine the status of cassava mosaic begomoviruses in Nigeria and to ascertain if the virulent Ugandan variant of East African cassava mosaic virus (EACMV-Ug2) was present. Of the 418 farms visited, 48% had cassava with moderately severe or severe symptoms, whereas 52% had cassava with mild symptoms. These distributions were at random. Of the 1,397 cassava leaf samples examined, 1,106 had symptoms. In polymerase chain reaction tests, 74.1% of the symptom-bearing samples tested positive for African cassava mosaic virus (ACMV) alone, 0.3% for EACMV alone, 24.4% for mixed infections by the two viruses, and 1.2% did not react with any of the primers used. The two viruses also were detected in 32% of the 291 symptomless plants and in the whitefly vector samples. EACMV-Ug2, Indian cassava mosaic virus, and South African cassava mosaic virus were not detected in any of the whitefly or leaf samples. Most farms had ACMV in single infection as well as in mixed infections with EACMV. Most doubly infected plants showed severe symptoms. Two biological variants of ACMV were identified based on symptom expression on cassava in the field. ACMV and EACMV were detected in the leguminous plant Senna occidentalis (L.) Link and the weed Combretum confertum Lams.; these are new natural hosts of the viruses. Although the virulent EACMV-Ug2 was not detected, the occurrence of variants of ACMV and a high proportion of mixed infections by ACMV and EACMV, which could result in recombination events such as the one that produced EACMV-Ug2, demands appropriate measures to safeguard cassava production in Nigeria.